Growth Performances of Photinia × fraseri Dress. Seedlings from Cuttings of Five Ortets in Different Districts - Özel, Halil Barış; Yücedağ, Cengiz; Ayan, Sezgin (Prensip Publishing, 2023)
With its impressive leaves and ability to resist harsh environmental conditions, Photinia × fraseri Dress., a hybrid species, is widely used in landscaping and has an ever-increasing economic and environmental value. The economic value of the landscape plants is directly proportional to their growth performance. For this reason, it is of great importance to identify and use the fastest growing ortet, especially in landscape plants in terms of cost and profitability. In this study, five ortets of P. × fraseri were compared in terms of their growth performances based on seedling height, root collar diameter, leaf length, leaf width, root length, root number, last shoot length, stem and root fresh-dry weights, and seedling fresh and dry weights. As a result of the study, it was found that the growth performances of five ortets in different districts were generally ranked as Eregli < Alapli < Ulus < Devrek < Zonguldak, and that the difference between the pairs of ortets in terms of some seedling characters reached up to 2.8 times. The study suggests that the selection of ortet is extremely important in seedling growth.
Keywords: 15. Life on land